Rancang Bangun Aplikasi Penentu Masa Subur Wanita Berbasis Android dengan Metode Keluarga Berencana Alamiah - Agustina, Dinda Ayu Dwi; Sunarto, M.J. Dewiyani; Romeo, Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
The failure rate acceptor Natural Family Planning (KBA) specifically calendar method is still high, cause there are a variety of factors. KBA principle used to determine the time of ovulation has also been applied by Muslims, Catholics and other religions that exist in Indonesia. Not only KBA alone, KB tool has also been applied to regulate births by all religious people in Indonesia. However, not all family planning tool used in Indonesia is approved by all religions. Permanent contraception, which trigger the prohibition of the use of contraceptives by the Islamic religion and the Catholic religion because already breaking the law (provisions) and religious laws.Solutions that can solve the problem, namely by the application of the determining woman's fertile period (APMS). APMS an application to determine the woman's fertile period is designed to use operation system (OS) android with methods of natural family planning (KBA). Operation System android is now more attractive to people because it can be reached by all circles.Analysis of the results of usability testing is performed by using a questionnaire based on ease of operations, accuracy of information and user satisfaction. Based test that directly tested usability testing to users expressed SIGNIFICANT application, so it can be concluded that this application has good usability and fit for use.